(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
Social media has become an integral part of our daily lives in today’s digital environment. Social media sites like Instagram, Tik Tok, and Twitter offer countless chances for self-expression, enjoyment, and communication. Despite these benefits, worries about social media’s potential detrimental effects on mental health are mounting. According to research, excessive internet use, particularly among teens and young people, can lead to problems including anxiety, melancholy, loneliness, and distorted body image. This article examines the effects of social media on mental health as well as the reasons it is still so alluring and addicting.